Maps based on electric analog model showing the net projected change in water levels resulting from pumping plan 2 and recharge plans A and B in Mill Creek Valley, Butler and Hamilton Counties, Ohio / [peta] (Washington, D C : Department of the Interior, 1970)
PSZJBL